ELViM: Exploring Biomolecular Energy Landscapes through Multidimensional Visualization - Viegas, Rafael Giordano [UNESP]; Martins, Ingrid B. S. [UNESP]; Sanches, Murilo Nogueira [UNESP]; Oliveira Junior, Antonio B.; Camargo, Juliana B. de [UNESP]; Paulovich, Fernando V.; Leite, Vitor B. P. [UNESP] (American Chemical Society (ACS), 2024)
Molecular dynamics (MD) simulations provide a powerful means of exploring the dynamic behavior of biomolecular systems at the atomic level. However, analyzing the vast data sets generated by MD simulations poses significant challenges. This article discusses the energy landscape visualization method (ELViM), a multidimensional reduction technique inspired by the energy landscape theory. ELViM transcends one-dimensional representations, offering a comprehensive analysis of the effective conformational phase space without the need for predefined reaction coordinates. We apply the ELViM to study the folding landscape of the antimicrobial peptide Polybia-MP1, showcasing its versatility in capturing complex biomolecular dynamics. Using dissimilarity matrices and a force-scheme approach, the ELViM provides intuitive visualizations, revealing structural correlations and local conformational signatures. The method is demonstrated to be adaptable, robust, and applicable to various biomolecular systems.